2017
DOI: 10.1371/journal.pone.0173152
|View full text |Cite
|
Sign up to set email alerts
|

Measuring scientific impact beyond academia: An assessment of existing impact metrics and proposed improvements

Abstract: How does scientific research affect the world around us? Being able to answer this question is of great importance in order to appropriately channel efforts and resources in science. The impact by scientists in academia is currently measured by citation based metrics such as h-index, i-index and citation counts. These academic metrics aim to represent the dissemination of knowledge among scientists rather than the impact of the research on the wider world. In this work we are interested in measuring scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
110
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 24 publications
2
110
0
5
Order By: Relevance
“…Large-scale, systematic studies of altmetrics are necessary to reveal evidence of their validity as an impact indicator (Haustein, Peters, Sugimoto, Thelwall, & Larivière, 2014). In this study, (following earlier studies by Bornmann, 2014bBornmann, , 2015bRavenscroft et al, 2017), we address the question of convergent validity of altmetrics data for indexing societal impact by:…”
Section: Figure 1 Results Of a Random Effects Meta-analysis Of Ninementioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale, systematic studies of altmetrics are necessary to reveal evidence of their validity as an impact indicator (Haustein, Peters, Sugimoto, Thelwall, & Larivière, 2014). In this study, (following earlier studies by Bornmann, 2014bBornmann, , 2015bRavenscroft et al, 2017), we address the question of convergent validity of altmetrics data for indexing societal impact by:…”
Section: Figure 1 Results Of a Random Effects Meta-analysis Of Ninementioning
confidence: 99%
“…In the UKREF, societal impact assessments are now a budget-relevant part of evaluation (NISO Alternative Assessment Metrics Project, 2014). By implication, impact assessment in the REF (and other similar national evaluation procedures) is about a social contract: "a relationship through which researchers gain funding in return for contributing to society"(Terama et al, 2017) Ravenscroft et al (2017). investigated whether altmetrics might replace reviewers' assessments of societal impact by focusing on references cited in case studies.…”
mentioning
confidence: 99%
“…Finally, as a limitation of our work, we emphasise that we do not consider the broader societal, cultural, and economic impact that is also evaluated in the REF. Such a broader evaluation cannot be done on the basis of metrics (Ravenscroft et al, 2017;Bornmann, Haunschild, and Adams, 2018;Pollitt et al, 2016) and should therefore be carried out using peer review. Outputs that are not covered in bibliographic databases such as the WoS, Scopus, Dimensions, and Microsoft Academic also need to be assessed by peer review.…”
Section: Discussionmentioning
confidence: 99%
“…Chakraborty et al [5] showed that the change in yearly citation count of articles published in journals is different from articles published in conferences. Even the evolution of yearly citation count of papers varies across disciplines [6,34]. This further raises a new proposition of designing domain-specific impact measurement metrics.…”
Section: Citation Count As Impact Measurementioning
confidence: 99%